Comparaison de deux « populations » de la deuxième moitié du Ve millénaire avant notre ère : approche anthropométrique - Aude Civetta; Aurore Schmitt; Bérangère Saliba-serre; Jean-Luc Gisclon; Gilles Loison (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Recently, some phenotypic features of Middle Neolithic populations, observed on series from old archaeological excavations, have been challenged. In order to characterize skeleton size and shape variability of Middle Neolithic individuals, we studied the osteological series from the necropolis of pontcharaud 2; this site is dated from the second half of the 5th millenium and located in the “Massif central”.Concerning the skull dimensions, differences between sexes are weak. The values of indexes are more homogeneous in males than in females. Concerning the long bones dimensions, sexual dimorphism is rather pronounced and most of males are robust.This series was compared to the collection of one from Le Crès, a contemporary settlement in south of France. Sexual dimorphism of this group follows the same trend than the one of Pontcharaud 2. The format of the long bones best distinguishes the two series, especially in females. Differences in shape, expressed by pilastric and platycnemic indexes, are probably related to the way of life that induces different type of mobility and physical activities.The present study showed unexpected metric features for Middle Neolithic populations: pronounced post-cranial sexual dimorphism, males’ robustness and high variability of statures. However, it is necessary to complete this research by studying non metric anatomical variation on the one hand and diet by stable isotopic analysis on the other hand; this will allow us to precise and interpret the differences between both series.